EFEKTIVITAS MEDIA GOOGLE SITES TERHADAP HASIL BELAJAR SISWA - Elya Salma Yasmina; Siska Sukma Ayu Liatul Fitria; Alan Mustapa; Jarot Tri Bowo Santoso; Kardiyem (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low Mid-Semester Assessment results of class X-E students, which only achieved an average of 65.06, with 30.56 percent of students achieving completeness while 64.44 percent did not meet the Learning Objective Achievement Criteria. This condition indicates the need for efforts to improve learning outcomes through the use of more interactive digital learning media. This study aims to determine the effectiveness of using Google Sites on student learning outcomes in Economics. This study used a quantitative research method with a one-group pre-test and post-test design. The study sample consisted of 31 students who took the pre-test and post-test. The results showed an increase in the average score from 58.22 to 90.16 after using Google Sites. The Wilcoxon test results showed a significant difference in the average score between the pre-test and post-test scores. In addition, the N-Gain test result of 75 is in the sufficient category. Based on these results, the use of Google Sites has proven effective on student learning outcomes and can be used as a digital learning medium in Economics.